Factors in ensuring construction readiness in sarawak’s building construction - Nurul Asyilah, Romzi (2024)
Construction readiness is determined as the main contributor to delay in construction. It is vital to determine the activities and procedures that should be completed prior to construction kick off. These delays often lead to increase of costs, putting contractors at risk. They suffer losses as a result of the project rather than gains. This is because project teams tend to rush into construction without assessing the readiness of the project. Therefore, it is necessary to evaluate a project's readiness. The goal of this research is to examine Sarawak's construction readiness for upcoming development projects. This study aims to accomplish three objectives that have been identified in the study. Firstly, identify the factors influencing the construction project's readiness for implementation. Secondly, rank the critical readiness factors for the project's implementation in Sarawak. Thirdly, categorize the critical construction readiness factors for building projects in Sarawak. In stage one of the studies, the questionnaire is developed from the identified Construction Readiness Factor (CRF), from the literature review. In stage two, the CRFs are ranked based on data analysis from ninety-one replies using the Relative Importance Index (RII). Stage three involves categorizing the critical construction readiness factors. This study focuses on Sarawak's building construction projects. A total of thirty-seven critical CRF for building construction projects are identified. The critical CRF are categorized into four groups, which are “preliminary work and authorities approval”, “procurement and execution,” “documentation and verification” and “capability and project scope”. To sum up, construction readiness is necessary not just at the start of the project but also during the early phase. These CRFs can assist researchers in creating a construction readiness assessment tool for building construction projects, as well as assist industry practitioners in evaluating the readiness of their projects through guideline, framework and checklist.